Singaporean Youths Must Have Wings And Yet Know Where Their Nest Is - Tarulevicz, Nicole (Penerbit Universiti Sains Malaysia (USM Press), 2010)
Young people generally form the future of any nation state and Singapore is no exception, it is, however, especially concerned about the future of itself as a nation. For Singapore the theme of youth is doubled, as the newness of the nation is a mirrored reflection of young Singaporeans and for the state. Young people embody the fragility of the nation itself, and government policy towards them has become a site where anxiety about the future of the nation is expressed. "Singaporean youths must have wings and yet know where their nest is" interrogates selected policies directed at young people in the city-state of Singapore against the backdrop of the youth of that nation-state itself. This examination includes: policies towards young offenders (and criminality generally), highlighting the anxiety the state feels about the non-conformity of young law-breakers and about the othering of criminals, about the role of National Service as a mechanism for masculinised nation building, and about the definition and discourse around post-independence generations, including the "brain drain" generation, the "Generation Millennium", and the "quitters and stayers", illustrating Singaporean tension between nationalism and political apathy. The resulting analysis questions the notion of youth as agents of change, troubles ideas of technology as a mechanism for liberalisation in Singapore, and challenges Western assumptions about the liberalising power of affluence and globalisation.